Conformity of Land Use with Spatial Pattern and Direction of Green Open Space Development in South Bengkulu Regency: Keselarasan Penggunaan Lahan dengan Pola Ruang dan Arahan Pengembangan Ruang Terbuka Hijau di Kabupaten Bengkulu Selatan - Sitorus, Santun R.P.; Mustamei, Engge; Mulya, Setyardi Pratika (Jurnal Ilmu Tanah dan Lingkungan, 2019)
Bengkulu Selatan Regency is a region that continues to grow, as evidenced by the submission of Manna to become a city. Land use must always be evaluated by referring to the regional spatial plan (RTRW). In accordance with the Spatial Planning Law No. 26 of 2007, one must be at least green open space (RTH) (30%) consisting of public green space (20%) and private green space (10%). This study aims to identify existing land use (2018), to evaluate land use confirmity with the spatial plan, to know the type and extent of GOS spreading (Kota Manna), to prepare the direction of GOS development plan. The method used is the analysis of geographic information systems, logical alignment matrices, and descriptive. The results showed that the three largest existing land uses were 55,861.0 ha of forest (47.91%), 43,186.7 ha of plantation (37.04), and 7,257.8 ha of rice fields (6.23%). The area of land use that is in conformed with the spatial pattern of RTRW is 84,823.7 ha (73%), transition is 27,115.0 ha (23%), and is not conformed at 4,648.0 ha (4%). Appropriate land use is recommended to continue and not conformed land use is advisable to be stopped for further development. The existing public GOS is still less (-23.2 ha) based on the size of the area, but it has exceeded the needs based on the population (2,515.3 ha). The development of public green space can be done on the first priority land with an area of 38.6 ha because it is sufficient for the needs of public GOS based on an area, directives for control of spatial use are carried out with four instruments, namely zoning regulations must be immediately made to establish space allocation zones, licensing must be more tightened in accordance with the direction of space allocation, carry out control of providing incentives and disincentives, by making operational guidelines in its implementation, and applying sanctions to every violator to cause a deterrent effect